2017
DOI: 10.1371/journal.pone.0182710
|View full text |Cite
|
Sign up to set email alerts
|

The risks of hepatocellular carcinoma development after HCV eradication are similar between patients treated with peg-interferon plus ribavirin and direct-acting antiviral therapy

Abstract: The risk of hepatocellular carcinoma (HCC) development is reduced following viral elimination by interferon therapy in chronic hepatitis C patients. However, the risk in patients treated with interferon-free direct-acting antivirals (DAAs) is unknown. We evaluated chronic hepatitis C patients who achieved viral eradication by pegylated-interferon plus ribavirin (PEG-IFN/RBV, n = 244) or daclatasvir plus asunaprevir (DCV/ASV, n = 154) therapy. None of the patients had prior history of HCC or antiviral therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 36 publications
4
57
0
Order By: Relevance
“…As the baseline characteristics of the patients differed between the two groups, we used PS matching to resolve these differences. Two studies compared the occurrence rate of HCC between patients receiving IFN‐based and IFN‐free treatments by using PS matching . In these studies, assessments of liver histology, which is a gold standard diagnostic tool for evaluating liver fibrosis, were not considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the baseline characteristics of the patients differed between the two groups, we used PS matching to resolve these differences. Two studies compared the occurrence rate of HCC between patients receiving IFN‐based and IFN‐free treatments by using PS matching . In these studies, assessments of liver histology, which is a gold standard diagnostic tool for evaluating liver fibrosis, were not considered.…”
Section: Discussionmentioning
confidence: 99%
“…More factors included in the analysis can achieve greater accuracy, but require more patients. In previous studies using PS matching, platelet count or Fibrosis‐4 index was included as an index of liver fibrosis, although the stage of liver fibrosis by liver biopsy was not considered as a variable, and the number of patients before PS matching was small …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the risk of HCC occurrence following treatment with DAAs was reported to be 2.96/100 patients per year, while Kanwal noted that no evidence was found to suggest that DAAs promote HCC in a large study of 22 500 patients . More recently, no evidence for differential HCC occurrence risk following SVR between DAA and IFN‐based therapy was found . On the other hand, although the risk of HCC after achieving SVR has been reported to be high in patients with established LC, an easy and simple strategy for determination of those with high risk for development of HCC after reaching SVR24 with DAA therapy is required.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that the incidence of HCC was reduced after eradication of HCV in patients treated with DAAs . Furthermore, Ikeda et al reported on HCC recurrence rates in patients after curative treatment for HCC who had and had not received antiviral therapy.…”
Section: Introductionmentioning
confidence: 99%